2023
DOI: 10.1007/s10557-023-07437-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Fractional Flow Reserve Measured Immediately After Percutaneous Coronary Intervention

Abstract: Purpose The purpose of the present study was to find the independent predictors of Fractional Flow Reserve (FFR) measured immediately after percutaneous coronary intervention with drug-eluting stent implantation (post-PCI FFR) and investigate if applying vessel-specific post-PCI FFR cut-off values to predict target vessel failure (TVF), a composite of cardiac death (CD), non-fatal myocardial infarction (MI) and target vessel revascularization (TVR), or a composite of CD and MI ameliorated its pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The possible reason is that stent underexpansion and residual lesions are significantly correlated with pressure drop, both of which may result in low physiological function value and lead to poor prognosis ( 9 , 33 ). Therefore, in conjunction with luminal imaging-guided stent optimization, post-PCI OFR can provide insight into the potential benefit of additional PCI strategies in improving clinical outcomes ( 34 , 35 ). Previous research has indicated a direct correlation between low post-PCI FFR and future adverse cardiac events ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible reason is that stent underexpansion and residual lesions are significantly correlated with pressure drop, both of which may result in low physiological function value and lead to poor prognosis ( 9 , 33 ). Therefore, in conjunction with luminal imaging-guided stent optimization, post-PCI OFR can provide insight into the potential benefit of additional PCI strategies in improving clinical outcomes ( 34 , 35 ). Previous research has indicated a direct correlation between low post-PCI FFR and future adverse cardiac events ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in conjunction with luminal imaging-guided stent optimization, post-PCI OFR can provide insight into the potential benefit of additional PCI strategies in improving clinical outcomes ( 34 , 35 ). Previous research has indicated a direct correlation between low post-PCI FFR and future adverse cardiac events ( 34 ). The specific cutoff value for post-PCI FFR may vary depending on factors such as the target lesion, vessel, and characteristics of the patients included in each study.…”
Section: Discussionmentioning
confidence: 99%